2023
DOI: 10.1039/d2re00271j
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of unexpectedly complex reaction pathways for the Knorr pyrazole synthesis via transient flow

Abstract: Kinetic data for reactions between phenyl hydrazine and 1,3-diketones (Knorr pyrazole synthesis) were acquired by using transient flow methods. Supported by further spectroscopic and mass spectrometry data, a microkinetic model...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…A previously described flow reactor system 3 was modified for this work (Fig. S1†), by integrating a (GC) oven to implement precise temperature ramps, and an on-line HPLC system to monitor and quantify multiple reaction species in an accessible manner.…”
Section: Resultsmentioning
confidence: 99%
“…A previously described flow reactor system 3 was modified for this work (Fig. S1†), by integrating a (GC) oven to implement precise temperature ramps, and an on-line HPLC system to monitor and quantify multiple reaction species in an accessible manner.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitive analytical methods have also enabled extremely high-throughput droplet screening in flow, , only possible because robust MS data can now be obtained from nanogram quantities. Combining such experiments with autonomous algorithms offers an extremely powerful route to reaction screening and optimization; here, the backlog becomes data processing and, potentially, generating new hypotheses to test.…”
Section: Is There Room For Innovation?mentioning
confidence: 99%
“…Typically, such measurements are taken under steady state conditions to allow for stable measurement. However, methods have been recently reported that use transient flow measurements without reaching steady state; parameters are continually varied to rapidly explore the impact of, e.g., temperature on kinetics. This powerful technique dramatically shortens the experimental time needed to extract useful information about a process, resulting in many data points from a single run …”
Section: Is There Room For Innovation?mentioning
confidence: 99%
“…[12][13][14][15] Dynamic experiments have been developed and demonstrated by various groups, but, thus far, used exclusively for homogeneous reactions. [16][17][18][19][20][21][22][23][24] Application of this technique to heterogeneously-catalyzed gas-liquid reactions, however, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%